Stanhopeinae Mesoamericanae II (Orchidaceae). Dos especies nuevas: Polycycnis blancoi y Coryanthes maduroana - Gerlach, Günter (Lankesteriana: International Journal on Orchidology, 2016)
Two new species of Stanhopeinae (Orchidaceae) are described and illustrated in this paper: Polycycnis blancoi, from Costa Rica, and Coryanthes maduroana from Panama.